Analysis of Liberal Feminism Elements in the Korean Drama "Extraordinary Attorney Woo" by Yoo In-shik - Fermawati; Suhardi; Testy Ariance Loren, Fabio (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2025)
This research aims to describe the form of liberal feminism in the Korean drama Extraordinary Attorney Woo by Yoo In-shik. This research uses a qualitative descriptive method with a qualitative approach. The data obtained is in the form of dialogue excerpts that describe aspects of liberal feminism in the drama. The data source in this research is the Korean drama Extraordinary Attorney Woo which consists of 16 episodes, each 1 hour 20 minutes long, which are watched via the Bstation application. The data collection technique applied is documentation technique. The results of the analysis show that there are form of liberal feminism which include classical liberal feminism, welfare liberal feminism, and contemporary liberal feminism.